Potensi Daun Jambu Biji sebagai Agen Antiinflamasi untuk Perawatan Trauma Puting pada Ibu Menyusui: Literature Review - Husna, Dewi Asmaul; Wijayanti, Krisdiana; Susanto, Edy (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT  Trauma to the nipple such as excoriation (abrasions), hyperemia, and fissures is often one of the main reasons mothers stop breastfeeding. Therefore, proper treatment is needed to prevent this condition. Research related to non-pharmacological therapy as an effort to treat nipple trauma has been conducted, one of which is by utilizing plants containing flavonoids that function as anti-inflammatory agents. This study aims to examine the potential of guava leaves as an anti-inflammatory agent that can be used as an alternative treatment for nipple trauma. This article adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as a guideline. The database was taken from Science Direct, PubMed, and Google Scholar. The search was conducted using keywords such as "psidium guava" or "wound healing" or "psidium guava leaves antiinflamatory" or "Psidium guajava linn for wound". In this review, ten articles were analyzed to see the study design, objectives, results, and conclusions. The results of observations that have been made guava leaves have the potential as a medicine for nipple trauma because they contain flavonoids that act as anti-inflammatory. The results of observations that have been carried out show that guava leaves have the potential as a natural medicine to treat nipple trauma, thanks to their flavonoid content which has anti-inflammatory agen. Keywords: Nipple Trauma, Flavonoids, Anti-inflamatory, Guajava Leaves  ABSTRAK Trauma pada puting seperti ekskoriasi (lecet), hiperemia, dan fisura sering menjadi salah satu alasan utama ibu menghentikan pemberian ASI. Oleh karena itu, diperlukan penanganan yang tepat untuk mencegah kondisi tersebut. Penelitian terkait terapi non-farmakologi sebagai upaya pengobatan trauma puting telah dilakukan, salah satunya dengan memanfaatkan tanaman yang mengandung flavonoid berfungsi sebagai agen antiinflamasi. Penelitian ini bertujuan untuk mengkaji potensi daun jambu biji sebagai agen antiinflamasi yang dapat digunakan sebagai alternatif pengobatan trauma puting. Penelitian ini menggunakan metode Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA). Database diambil dari Science Direct, PubMed, dan Google Scholar. Pencarian dilakukan dengan menggunakan kata kunci seperti "psidium guava leaves" atau "wound healing" atau "psidium guajava leaves antiinflamasi" atau “daun jambu biji untuk luka”. Dalam tinjauan ini, sepuluh artikel dianalisis untuk melihat desain penelitian, tujuan, hasil, dan kesimpulan. Hasil tinjauan yang telah dilakukan menunjukkan bahwa daun jambu biji memiliki potensi sebagai obat alami untuk mengatasi trauma pada puting susu. Hal ini dikarenakan daun jambu biji mengandung flavonoid yang memiliki sifat antiinflamasi. Kata Kunci: Trauma Puting, Flavonoids, Anti-inflamasi, Daun Jambu Biji